Plasmonic piezoelectric nanomechanical resonator for spectrally selective infrared sensing - Hui, Yu (Nat Commun, 2016)
Ultrathin plasmonic metasurfaces have proven their ability to control and manipulate light at unprecedented levels, leading to exciting optical functionalities and applications. Although to date metasurfaces have mainly been investigated from an electromagnetic perspective, their ultrathin nature may also provide novel and useful mechanical properties. Here we propose a thin piezoelectric plasmonic metasurface forming the resonant body of a nanomechanical resonator with simultaneously tailored optical and electromechanical properties. We experimentally demonstrate that it is possible to achieve high thermomechanical coupling between electromagnetic and mechanical resonances in a single ultrathin piezoelectric nanoplate. The combination of nanoplasmonic and piezoelectric resonances allows the proposed device to selectively detect long-wavelength infrared radiation with unprecedented electromechanical performance and thermal capabilities. These attributes lead to the demonstration of a fast, high-resolution, uncooled infrared detector with ∼80% absorption for an optimized spectral bandwidth centered around 8.8 μm.